A Combination of Impulsivity Subdomains Predict Alcohol Intoxication Frequency. (15th June 2018) - O'Halloran, Laura; Pennie, Brian; Jollans, Lee; Kiiski, Hanni; Vahey, Nigel; Rai, Laura; Bradley, Louisa; Lalor, Robert; Whelan, Robert
Abstract : Background: Impulsivity, broadly characterized as the tendency to act prematurely without foresight, is linked to alcohol misuse in college students. However, impulsivity is a multidimensional construct and different subdomains likely underlie different patterns of alcohol misuse. Here, we quantified the association between alcohol intoxication frequency and alcohol consumption frequency and choice, action, cognitive, and trait domains of impulsivity. Methods: University student drinkers ( n  = 106) completed a battery of demographic and alcohol‐related items, as well as self‐report and task‐based measures indexing different facets of impulsivity. Two orthogonal latent factors, intoxication frequency and alcohol consumption frequency, were generated. Their validity was demonstrated with respect to adverse consequences of alcohol use. Machine learning with penalized regression and feature selection was then utilized to predict intoxication and alcohol consumption frequency using all impulsivity subdomains. Out‐of‐sample validation was used to quantify model performance. Results: Impulsivity measures alone were significant predictors of intoxication frequency, but not consumption frequency. Propensity for increased intoxication frequency was characterized by increased trait impulsivity, including the Disinhibition subscale of the Sensation Seeking Scale, Attentional and Non‐planning subscales of the Barratt Impulsiveness Scale, increased task‐based cognitive impulsivity (response time variability), and increased choice impulsivity (steeper delay discounting on a delay discounting questionnaire). A model combining impulsivity domains with other risk factors (gender; nicotine, cannabis, and other drug use; executive functioning; and learning processes) was also significant but did not outperform the model comprising of impulsivity alone. Conclusions: Intoxication frequency, but not consumption frequency, was characterized by a number of impulsivity subdomains. Abstract : Individual differences in different aspects of impulsivity significantly predicted alcohol intoxication frequency but not consumption frequency. The three subcategories that supported a tendency toward more frequent intoxication were called trait impulsivity (attentional, nonplanning, disinhibition, and experience seeking), questionnaire‐based choice impulsivity (delay discounting), and task‐based cognitive impulsivity (sustained attention). The findings support the view that different components of impulsivity contribute to different patterns of alcohol misuse.